Aplicación de Aspen Custom Modeler (ACM) en la fermentación del residuo mucilaginoso de cacao CCN-51 : Aplicación de Aspen Custom Modeler (ACM) en la fermentación del residuo mucilaginoso de cacao CCN-51 - Delgado Noboa, Jorge Washington; Soler, Jaime; Peña, José Ángel (Jornada de Jóvenes Investigadores del I3A, 2021)
The residual biomass has not been fully valued and used in Ecuador from the energy point of view. An example of this is the cocoa mucilage, which is currently a waste without useful and profitable use. However, it represents a high energy potential in the production of bioethanol for use as an additive in gasoline, resulting in a possible replacement for fossil fuels [1]. The objective of this study was the use of the Aspen Custom Modeler (ACM) software to model the production of bioethanol generated in the fermentation of Cacao CCN-51 mucilage, applying the kinetic model of Andrew and Levenspiel [2].